Transformative higher education for Atmanirbhar Bharat: Reimagining the universities of future - Mantha, S. S. (University News)
A University is a community of teachers and scholars. It must nurture academic freedom. A student must explore the spirit of adventure and innovation in a university. Knowledge and learning are the media. A certificate of attainment is the fruit she seeks. The Boundary conditions, however, have been changing the contours of a traditional university. Some pressure points are a large number of students, inadequate faculty numbers, poor faculty quality and shrinking job opportunities. Each pressure point has a unique pressure release mechanism that is Atmanirbharata.- Reproduced